2018
DOI: 10.1128/mbio.01408-18
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic Protections against Human-Infecting Avian Influenza Viruses Correlate to Biased Cross-T-Cell Responses

Abstract: Against a backdrop of seasonal influenza virus epidemics, emerging avian influenza viruses (AIVs) occasionally jump from birds to humans, posing a public health risk, especially with the recent sharp increase in H7N9 infections. Evaluations of cross-reactive T-cell immunity to seasonal influenza viruses and human-infecting AIVs have been reported previously. However, the roles of influenza A virus-derived epitopes in the cross-reactive T-cell responses and heterosubtypic protections are not well understood; un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
1
18
0
3
Order By: Relevance
“…Screening of immunogenic peptides which are presented by specific MHC I molecules is crucial for the development of vaccines for infection diseases or cancer immunotherapy and for T-cell immune response evaluation (45)(46)(47)(48)(49)(50)(51). Recently, several pre-clinical and clinical studies have shown that vaccines targeting predicted personal tumor neoantigens are feasibility, safety, and immunogenicity (45,50,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Screening of immunogenic peptides which are presented by specific MHC I molecules is crucial for the development of vaccines for infection diseases or cancer immunotherapy and for T-cell immune response evaluation (45)(46)(47)(48)(49)(50)(51). Recently, several pre-clinical and clinical studies have shown that vaccines targeting predicted personal tumor neoantigens are feasibility, safety, and immunogenicity (45,50,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…细胞免疫水平明显低于针对2009 pH1N1本身的T细胞 免疫 [12,13] . 在2009 pH1N1与多种禽流感的交叉T细胞 免疫研究中发现, 与NP相比, M1 蛋白对于不同流感亚 型的免疫原性差异贡献更大, 而这种交叉T细胞免疫反 应所产生的保护作用也在动物试验中得到了证实 [12] . 在2009 pH1N1与H7N9的M1蛋白中, 我们和国际 上其他研究组已经鉴定了一系列能够激发不同HLA超 级型个体T细胞免疫反应的保守表位 [10,13~15] .…”
Section: Cd4unclassified
“…研究表明, 2009 pH1N1 感染之所以产生相对温和临床症状, 部分是因为季节 性流感病毒感染或疫苗接种产生了交叉免疫T细胞从 而产生保护效力 [11,22] . 季节性H1和H3甲型流感病毒感 染产生的记忆性T细胞对禽流感H5N1病毒具有交叉免 疫应答 [7,20] , 并且对H7N9也能产生CD4 + 和CD8 + T细胞 交叉免疫 [12,23,24] . 新型禽流感病毒H7N9具有哺乳动物 适应性的氨基酸替换, 与其从禽类到人类的宿主转换 相关 [1,25] , 同时该病毒蛋白序列上相应的T细胞表位存 在突变, 影响了人类免疫系统识别和病毒清除 [19] .…”
Section: 对保守的内部蛋白表位 流感病毒特异的Cd4unclassified
See 1 more Smart Citation
“… 2017 ; Zhao et al . 2018 ). More efforts should be paid to the development of new drugs and its corresponding clinical assessment.…”
mentioning
confidence: 99%